Hybrid access for femtocells based on contract theory - Jiao Xue; Jianting Yue (International Journal of Distributed Sensor Networks, 2016)
Femtocell is a promising technology for wireless communication in the near future, due to its benefits in improving indoor coverage and enhancing system throughput. Access control is a critical issue for both operator and mobile users, and there lie three choices including open, closed and hybrid access. Hybrid access seems to be a promising choice since the femtocell opens part of the resources for macrocell users while reserving the residual part for its own femtocell users. In this way, the femtocell helps improve the network performance without much sacrifice of its own utility. Meanwhile, the macrocell should offer adequate incentive to motivate the femtocells, otherwise the femtocells are unwilling to open their resources. As another challenging obstacle, the macrocell could hardly ask femtocells to truthfully reveal their private information which is important for hybrid access, thus the situation with asymmetric information happens. Contract theory is hereby introduced to deal with such a problem. In this article, we propose a mechanism for hybrid access control, wherein the macrocell remunerates certain amount of spectrum to femtocells according to their contribution of data rate to macrocell users. This design ultimately improves the service quality for macrocell users. After figuring out the sufficient and necessary conditions for feasible contract using contract theory, we further derive the optimal contract. We also discuss several issues due to the distinctive characteristics of our problem.